Methacrylate‐Modified Gold Nanoparticles Enable Noninvasive Monitoring of Photocrosslinked Hydrogel Scaffolds. Issue 7 (15th June 2022) - Li, Lan; Gil, Carmen J.; Finamore, Tyler A.; Evans, Connor J.; Tomov, Martin L.; Ning, Liqun; Theus, Andrea; Kabboul, Gabriella; Serpooshan, Vahid; Roeder, Ryan K.
Abstract : Photocrosslinked hydrogels, such as methacrylate‐modified gelatin (gelMA) and hyaluronic acid (HAMA), are widely utilized as tissue engineering scaffolds and/or drug delivery vehicles, but lack a suitable means for noninvasive, longitudinal monitoring of surgical placement, biodegradation, and drug release. Therefore, a novel photopolymerizable X‐ray contrast agent, methacrylate‐modified gold nanoparticles (AuMA NPs), is developed to enable covalent‐linking to methacrylate‐modified hydrogels (gelMA and HAMA) in one‐step during photocrosslinking and noninvasive monitoring by X‐ray micro‐computed tomography (micro‐CT). Hydrogels exhibit a linear increase in X‐ray attenuation with increased Au NP concentration to enable quantitative imaging by contrast‐enhanced micro‐CT. The enzymatic and hydrolytic degradation kinetics of gelMA‐Au NP hydrogels are longitudinally monitored by micro‐CT for up to 1 month in vitro, yielding results that are consistent with concurrent measurements by optical spectroscopy and gravimetric analysis. Importantly, AuMA NPs do not disrupt the hydrogel network, rheology, mechanical properties, and hydrolytic stability compared with gelMA alone. GelMA‐Au NP hydrogels are thus able to be bioprinted into well‐defined 3D architectures supporting endothelial cell viability and growth. Overall, AuMA NPs enable the preparation of both conventional photopolymerized hydrogels and bioprinted scaffolds with tunable X‐ray contrast for noninvasive, longitudinal monitoring of placement, degradation, and NP release by micro‐CT. Abstract : Methacrylate‐modified gold nanoparticles (AuMA NPs) are described as a novel photopolymerizable X‐ray contrast agent for covalent‐linking to methacrylate‐modified hydrogels (e.g., gelMA) in one‐step during photocrosslinking. AuMA NPs enable the preparation of hydrogels and bioprinted scaffolds with tunable X‐ray contrast for noninvasive, longitudinal monitoring of placement, degradation, and nanoparticle release by computed tomography.